Formation of mg-rich olivine pseudomorphs in serpentinized dunite from the Mesoarchean Nuasahi Massif, Eastern India: Insights into the evolution of fluid composition at the mineral-fluid interface - Majumdar, A.; Hövelmann, J.; Vollmer, C.; Berndt, J.; Mondal, S.; Putnis, Andrew (Oxford University Press, 2016)
We present a detailed investigation of the micrometer-to nanometer-scale textural-chemical features in partially serpentinized dunites from the lower ultramafic unit of the Mesoarchean Nuasahi Massif, eastern India; these data are used to interpret the evolution in fluid chemistry at the reaction interface during progressive hydration of olivine. In the first stage of serpentinization, a mixed layer of Mg-rich lizardite + brucite+magnetite formed within fractures producing a typical mesh texture, followed by homogeneous brucite-free lizardite at the inner interface of the mixed layer. A unique feature of the serpentinization in the Nuasahi dunites, which to our knowledge has not been previously described, is the formation of a pseudomorphic rim of Mg-rich olivine (Fo98) directly in contact with the primary olivine (Fo92). The textural-chemical relations, such as (1) sharp but irregular textural-chemical reaction interfaces, (2) propagation of replacement fronts along fractured pathways, allowing transfer of aqueous species towards the center of olivine crystals, and (3) the presence of micro-to nano-porosity within product phases, indicate that each replacement process was governed by an interface-coupled dissolution-precipitation mechanism. Additionally, Mg-rich chromite, distributed within the samples, was partially pseudomorphically replaced by an Fe-rich chromite rim and/or isolated magnetite. Mass-balance calculations for different replacement reactions suggest that lizardite formation reactions may be coupled with chromite replacement reactions, allowing a micrometer-scale transfer of aqueous species (e.g. Al3+, Cr3+) between chromite and olivine reaction interfaces. The lizardite formation reactions have produced hierarchical patterns of reaction-induced fractures within primary olivine crystals and the replacement front has progressed from the outer rim towards the center of the olivine grain. The sequential formation of different pseudomorph phases during progressive hydration of primary olivine reflects a micrometer-scale variation in silica and/or water activity in the precipitating solution across the reaction interface, and may also be associated with a decrease in temperature. The Fe2+Mg-1 chemical exchange potential of the equilibrating system at the reaction interface also plays an importantrole, controlling the Fe/Mg ratio of the secondary minerals and the molar proportions of magnetite. The pattern of fluid-mobile element mobilization (e.g. Li, B) during replacement suggests that serpentinization of the Nuasahi dunite occurred during interaction with a B-rich solution, possibly in an ocean-floor setting.